Gait biomechanics and tibial stress fracture in runners - Milner, C. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Stress fractures are a common injury in athletes in general, and runners in particular. Stress fractures are a chronic, or overuse, injury resulting from fatigue damage to the bone. They occur when the damage accumulated due to the repeated application of physiological loads exceeds the capacity of the bony tissue to repair itself. The incidence of stress fractures in athletic populations is up to 50% (Brukner et al., 1996). Tibial stress fractures in particular are very common in recreational and competitive runners and military recruits. The tibia is the most common site of stress fracture in distance runners, accounting over 40% of all stress fractures (Brukner et al., 1996). The typical recovery time from a stress fracture is between 6 and 12 weeks. This includes periods of rest and reduced activity, to allow the natural reparative process of bone to take place at a rate exceeding that of damage accumulation. Reduced training capacity for a period of two to three months is a significant amount of time for both runners and military recruits. Therefore, identification of injury mechanisms and the prevention of stress fractures in runners is an important area of study.